2022
DOI: 10.1159/000526977
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Phase 2 Study of 5-Aminolevulinic Acid Hydrochloride and Sodium Ferrous Citrate for the Prevention of Nephrotoxicity Induced by Cisplatin-Based Chemotherapy of Lung Cancer

Abstract: Introduction: Cisplatin-based chemotherapy was established in the 1980s, and it has been improved by the development of a short hydration protocol in lung cancer therapy. However, cisplatin-based chemotherapy is still associated with renal toxicity. Because 5-aminolevulinic acid (5-ALA) with sodium ferrous citrate (SFC) is known to be a mitochondrial activator and a heme oxygenase-1 (HO-1) inducer, 5-ALA with SFC is speculated to mitigate cisplatin-induced renal inflammation. Methods: We investigated the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…ALA treatment may exert a protective role in cardiomyocytes under lenvatinib stimulation. In addition, ALA also promoted the function of cisplatin-based chemotherapy in the treatment of lung cancer [20], and ALA also reduced the production of proinflammation cytokines, which benefits IBD (Inflammation Bowel Disease) treatment [21]. A recent study also showed that ALA reduced the doxorubicin-induced ferroptosis and cardiotoxicity in cardiomyocytes [22].…”
Section: Discussionmentioning
confidence: 98%
“…ALA treatment may exert a protective role in cardiomyocytes under lenvatinib stimulation. In addition, ALA also promoted the function of cisplatin-based chemotherapy in the treatment of lung cancer [20], and ALA also reduced the production of proinflammation cytokines, which benefits IBD (Inflammation Bowel Disease) treatment [21]. A recent study also showed that ALA reduced the doxorubicin-induced ferroptosis and cardiotoxicity in cardiomyocytes [22].…”
Section: Discussionmentioning
confidence: 98%